ANALYZING HOTS TYPE – CRITICAL THINKING TEST BASED ON EDUCATION FOR SUSTAINABLE DEVELOPMENT AT ELEMENTARY SCHOOL - Neneng Widya Sopa Marwa; Ghullam Hamdu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to find out the development of bilingual picture book media as a tool of literary appreciation for grade IV elementary school students, to determine the feasibility of the bilingual picture book, and to identify students’ responses to the media. This research was conducted at SDN Kotasari involving 22 students in class IV-A, with 10 students participating in a limited trial. The type of research referred to the Borg and Gall model modified by Sugiyono, consisting of six stages, namely problem analysis, data collection, product design, design validation, design revision, and product trial. The instruments used were questionnaires for media validation by lecturers and student questionnaire sheets. Based on the data analysis, several findings were obtained: the quality of the bilingual picture book was categorized as very feasible with a percentage of 86% according to two media experts, 82.5% according to two linguists, and 91.5% according to two material experts. The percentage from the students’ responses was 89%, categorized as very good. Thus, it was concluded that the bilingual picture book media could be used in learning literary appreciation for grade IV elementary school students.